Synthesis, evaluation, and computational chemistry of novel selenenyl sulfides as 3C protease inhibitors with strong cell-based antiviral activity - Jin-Yin Tang; Shengwang Dai; Xiaofang Wang; Mengting Zhang; Jin-Rui Shi; Yong-Xuan Hong; Zhi-Juan Sun; Huan-Qin Dai; Jian-Guo Wang (Arabian Journal of Chemistry, 2024)
The 3C protease (3Cpro) is an important enzyme for developing therapeutic medicines against some severe viral infections. In order to discover new classes of antiviral agents, 42 novel selenenyl sulfides were prepared and characterized by 1H NMR, 13C NMR, 77Se NMR and HRMS. The target compounds demonstrated promising inhibitions against 3Cpro from either enterovirus 71 (EV71) or coxsackievirus B3 (CVB3), as well as desirable cell-based antiviral activity against these viruses. Among them, 11f displayed the most potent IC50 value of 0.28 ± 0.05 μM against EV71-3Cpro, and the strongest IC50 value of 0.72 ± 0.15 μM against CVB3, with a selectivity index of 51.5 against Hela cell, superior to the control drug rupintrivir. In addition, molecular docking was undertaken to predict a possible binding mode for compound 11f, and a comparative molecular field analysis (CoMFA) model was subsequently generated to understand the structure-activity relationships. Overall, the present research has provided some new insights to design a distinct family of antiviral compounds.